Attitude towards e-assessment: influence of gender, computer usage and level of education. (2nd September 2018) - Bahar, Mustafa; Asil, Mustafa
ABSTRACT: With astounding developments in online systems and education came the need for e-assessments of various forms. Despite plenty of studies about attitude towards computer-based and online education, attitude towards online assessment needs more focus due to scant research carried out. For this end, an e-assessment scale was used with a sample of 853 associate degree, undergraduate and graduate students to investigate the influence of gender, computer usage and level of education on attitude towards e-assessment. A mimic modelling approach was utilised following a confirmatory factor analysis, and the analysis found university students who used computers for a longer period of time had significantly higher scores on two e-assessment dimensions than those who used computers less. Males exhibited significantly more positive attitudes to e-assessment than females on test characteristics, individual characteristics and technical factors but not social and environmental factors. Level of education had no influence on attitude towards e-assessment.